The effect of the Ayas model to learning individual fast attack and high-order thinking skills of handball for students - Ali Radhi Abdul Hussein (Tanjungpura Journal of Coaching Research)
Background and Study Aim. The significance of this research lies in designing a specialized scale to evaluate advanced cognitive skills related to handball among students. It also examines the impact of the Ayas model on enhancing these higher-order thinking skills and teaching the technique of the individual fast attack in handball. This study aimed to investigate the effect of the Ayas Model on learning individual fast attack techniques and higher-order thinking skills in handball among students.